Challenges and lessons when using farmer knowledge in agricultural search and development projects in Africa - Asten, Piet J.A. van; Kaaria, Susan K.; Fermont, AM; Delve, Robert J. (Cambridge University Press, 2009)
Farmer participatory research (FPR) approaches are now considered mainstream and are especially applicable for developing appropriate technology options in complex, diverse and risk-prone regions, where local adaptations are crucial. Although the advantages of using farmer knowledge to guide scientific research are numerous and well documented, the challenges and potential pitfalls that befall biophysical researchers, in particular, when using FPR approaches have received much less attention, especially in sub-Saharan Africa. Our experiences show that in certain cases, the methods used to collect farmer knowledge are flawed, leading to inaccurate or incomplete information being gathered. This potentially leads to the development and promotion of unsustainable, unprofitable or socially unacceptable technologies. This paper uses a series of examples to illustrate that discrepancies between farmer and researcher observations may occur because (i) farmers and scientists may not have sufficient insight into the systems complexity, (ii) farmers and scientists use different reference frameworks, and (iii) methodological errors may lead to farmers intentionally or unintentionally providing false or ‘desired’ information to achieve (short-term) benefits. This paper concludes by providing guidelines to improve the integration of farmer and scientific knowledge in order to develop appropriate technology options that are both environmentally sound and adaptable to local conditions.